2020
DOI: 10.3390/met10101334
|View full text |Cite
|
Sign up to set email alerts
|

Metallurgical Effect of Rare-Earth Lanthanum Fluoride and Boride in the Composite Coating of Wires in the Arc Welding of Bainitic-Martensitic and Austenitic Steel

Abstract: For arc welding of high-strength and cold-resistant steels, the author developed an advanced design of steel wire with a micro-composite coating of a nickel matrix and nanoparticles of LaF3 and LaB6, which improves the metallurgical influence of rare-earth elements (REE) and forms refractory sulphides and oxides of REE, as well as boron nitride. The addition of 0.1–0.3 wt% La in the weld pool leads to an increase in the content of the refractory compounds La2O3, LaO2, and LaS, and to the reduction in the conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…It was widely used in the fluoride-glass ceramic [16,17], the scintillation crystals and rare earth crystal laser materials required by high-energy physics, nuclear medical imaging and industrial CT [18][19][20], arc lamp carbon electrode for lighting and other photoelectric fields, etc. [21][22][23]. Moreover, it has a low refractive index (1.4-1.6, compared with the Ge substrate) and low price.…”
Section: Introductionmentioning
confidence: 99%
“…It was widely used in the fluoride-glass ceramic [16,17], the scintillation crystals and rare earth crystal laser materials required by high-energy physics, nuclear medical imaging and industrial CT [18][19][20], arc lamp carbon electrode for lighting and other photoelectric fields, etc. [21][22][23]. Moreover, it has a low refractive index (1.4-1.6, compared with the Ge substrate) and low price.…”
Section: Introductionmentioning
confidence: 99%
“…Kataoka et al [36] reported the possibility of spray transfer in CO 2 using REM added wire. Parshin et al [37,38] achieved an increase in impact energy of welds in arc welding high-strength steels using composite coated wire with LaF 3 -LaB 6 . Parshin et al [39][40][41][42] investigated the positive effect of CaF 2 , AlF 3 , KBr, KF, NaCl, BaCl 2 , TiO 2 on increasing the melting coefficient of wires and improving the droplet transfer parameters in the MIG-, MAG-welding of steels and aluminum alloys.…”
Section: Introductionmentioning
confidence: 99%